2012
DOI: 10.2169/internalmedicine.51.6874
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab Used Successfully in the Treatment of Anti-NMDA Receptor Encephalitis

Abstract: We report the case of a young woman with anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis, without tumor, who was successfully treated with rituximab. Because conventional immunotherapy, including corticosteroids, immunoglobulin (IVIg), and plasma exchange showed little improvement in our patient, we introduced another treatment using rituximab. A week after the first administration of rituximab, her symptoms improved gradually and significantly. This case provides in vivo evidence that rituximab is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 26 publications
0
12
0
3
Order By: Relevance
“…Although several case reports have indicated that both rituximab and cyclophosphamide are quite effective alone (8-10), we administered these drugs in combination in the present case based on the recommendation of Dalmau et al (2), which resulted in a rapid clinical improvement in our patient. It is difficult to determine which regimen was more effective in this case, as previous reports have shown that both agents have an immediate effect on clinical symptoms (8,9). This immediate effect may result from the more selective suppression of the antibodysecreting function of B cells than that achieved with firstline immunotherapy.…”
Section: Discussionmentioning
confidence: 87%
“…Although several case reports have indicated that both rituximab and cyclophosphamide are quite effective alone (8-10), we administered these drugs in combination in the present case based on the recommendation of Dalmau et al (2), which resulted in a rapid clinical improvement in our patient. It is difficult to determine which regimen was more effective in this case, as previous reports have shown that both agents have an immediate effect on clinical symptoms (8,9). This immediate effect may result from the more selective suppression of the antibodysecreting function of B cells than that achieved with firstline immunotherapy.…”
Section: Discussionmentioning
confidence: 87%
“…A later report documented the condition in patients free of teratoma, and found that such patients may fare worse [4]. The anti-CD20 antibody rituximab has been used to successfully treat this condition [5], and has become the standard of care in refractory cases [6]. To our knowledge autopsy findings from a patient who fails to respond to rituximab therapy have not previously been reported.…”
Section: Introductionmentioning
confidence: 99%
“…For instance a woman with NMDARE, but without an associated tumor was treated with rituximab successful after conventional immunotherapy consisting of corticosteroids, IVIg, and plasma exchange resulted in little improvement. In her case, significant improvement was noted approximately one week after rituximab administration demonstrating the potential efficacy of these second line treatments in refractory [15].…”
Section: Case Presentationmentioning
confidence: 83%